1989
DOI: 10.1172/jci113992
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the subendothelial basement membrane during neutrophil diapedesis in an in vitro construct of a blood vessel wall.

Abstract: To examine the course of physiologic interactions between extravasating neutrophils and the subendothelial basement membrane, a model of the venular vessel wall was constructed by culturing human umbilical vein endothelial cells on a collagen matrix. After 21 d in culture, the endothelial cell monolayer displayed in vivo-like intercellular borders and junctions, deposited a single-layered, continuous basement membrane that was impenetrable to colloidal particles, and supported neutrophil extravasation in a phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
1
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(94 citation statements)
references
References 73 publications
2
89
1
2
Order By: Relevance
“…Although it is considered controversial (3,38), proteolytic cleavage of BM constituents is a commonly proposed mode of leukocyte penetration of BM barriers. Because the serine protease neutrophil elastase is known to be expressed on the cell surface of transmigrating neutrophils both in vitro (39) and in vivo (32) and has been implicated in neutrophil migration through the BM (17,32,39,40), the role of this protease in disruption of the BM in IL-1β-stimulated tissues was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is considered controversial (3,38), proteolytic cleavage of BM constituents is a commonly proposed mode of leukocyte penetration of BM barriers. Because the serine protease neutrophil elastase is known to be expressed on the cell surface of transmigrating neutrophils both in vitro (39) and in vivo (32) and has been implicated in neutrophil migration through the BM (17,32,39,40), the role of this protease in disruption of the BM in IL-1β-stimulated tissues was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Mackarel et al (159) found that neutrophil migration across cultured human pulmonary endothelium, and its associated subendothelial basement membrane was not affected by inhibitors of elastase or gelatinase. Similarly, Huber and Weiss (111) reported that neutrophil migration across human umbilical vein endothelial cells and their subtending basement membrane was not dependent on neutrophil elastase or cathepsin G and was resistant to inhibitors directed against neutrophil collagenase, gelatinase, and heparanase. Moreover, scanning electron microscopic examination of the transmigrated basement membrane showed no evidence of holes, even though basement membrane barrier function (as measured by the passage of monastral blue) was compromised.…”
Section: A Role For Proteases?mentioning
confidence: 92%
“…The presence of the endothelium was critical as denuded basement membranes did not support neutrophil migration. Because endothelial cells synthesize serine and metalloproteinases and are able to degrade basement membrane components, it was suggested that the endothelium prepared the basement membrane for neutrophil invasion (111). In any event, these studies provide compelling evidence that neutrophil proteases are not required for passage across the basement membrane.…”
Section: A Role For Proteases?mentioning
confidence: 99%
“…The process has long been thought to require local cell degradation of the basement membrane with matrix metalloproteinases (especially MTMMPs) and other enzymes. However, transmigration might also occur through mechanisms independent of proteolytic digestion (Huber and Weiss 1989). Cellular invadopodia may either transiently disrupt covalent and noncovalent linkages with local matrix disassembly or somehow breach small structural imperfections in the barrier.…”
Section: Basement Membranesmentioning
confidence: 99%